CREATIVE THINKING SKILLS FORMATION TECHNOLOGY - Nazarova Zubayda (The Conference Hub, 2025)
The article describes the full-fledged understanding of the general essence of the process of developing creative potential of its students, the creative technology of teaching, the object of personality creativity, the acquisition of the necessary knowledge, the criteria for dividing students into groups.
Keywords: creative technology, creative thinking, collaborative groups, flexible groups, thinking skills.